ANALISIS PENGARUH PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MEREK HONDA (Studi Pada Dealer Astra Motor Sumbawa Besar) - Tya Kartika Putri; Binar Dwiyanto Pamungkas (Fakultas Ekonomi dan Manajemen, 2022)
The purpose of this study was to determine the effect of consumer behavior on purchasing decisions for Honda motorcycles at the Astra Motor dealer, Sumbawa district. This type of research is associative research. The data used in this study is quantitative data obtained from primary sources. The number of samples in this study were 30 samples. The method used to collect data is through a questionnaire. The data analysis technique used simple linear regression analysis, t test and determinant coefficient test (R2). The results of the study show that consumer behavior has a positive and significant effect on purchasing decisions for Honda motorcycles at the Astra Motor Sumbawa Besar Dealer. The degree of influence of consumer behavior variables on purchasing decisions for Honda motorcycles at the Astra Motor Sumbawa Besar Dealer is 71.3%, while the remaining 28.7% is influenced by other variables outside this research model.